If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (19b + -7) + -9(2b + 2) = -7 Reorder the terms: (-7 + 19b) + -9(2b + 2) = -7 Remove parenthesis around (-7 + 19b) -7 + 19b + -9(2b + 2) = -7 Reorder the terms: -7 + 19b + -9(2 + 2b) = -7 -7 + 19b + (2 * -9 + 2b * -9) = -7 -7 + 19b + (-18 + -18b) = -7 Reorder the terms: -7 + -18 + 19b + -18b = -7 Combine like terms: -7 + -18 = -25 -25 + 19b + -18b = -7 Combine like terms: 19b + -18b = 1b -25 + 1b = -7 Solving -25 + 1b = -7 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '25' to each side of the equation. -25 + 25 + 1b = -7 + 25 Combine like terms: -25 + 25 = 0 0 + 1b = -7 + 25 1b = -7 + 25 Combine like terms: -7 + 25 = 18 1b = 18 Divide each side by '1'. b = 18 Simplifying b = 18
| 3x-2(2x+1)=8+4x | | 4b=908 | | 0.25m+3=4 | | 3-23=3x-8-2x | | -3-5x=-3 | | 2p^2+11p+9=0 | | 3x^2+6x=-15 | | y=2x^2+10x+12 | | 39=c-21 | | f(x)=5-8x | | 65=7x-2x+5 | | y=2x^2+20x+45 | | 2x=x+37 | | 4x-4=2x+50 | | y=30x+4 | | 16-4(-6)(3)= | | 2x-16i=-2-4yi | | m+12=19 | | 6+8x=6(1-6x) | | K^2-39k-40= | | Y-4=-2x-1 | | 3x-7=4x+2x+2 | | 12m-13=m+9 | | J^2+22j+40= | | 4(x-77)=3.14 | | 5(5x+4)=30 | | 4(x-77)=5 | | 6+2z=z-6 | | (73-2x)=(86-3x) | | 6+55x=44x+18 | | 5z+5=-20 | | 3.8=2s |